KECEPATAN EFEKTIF MEMBACA SISWA KELAS XI SEKOLAH MENENGAH ATAS NEGERI 1 SUNGAI AMBAWANG - Yeremia, Yulita (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Â AbstractThis thesis entitled Effective Speed Reading (KEM) Class XI student school SMA Negeri 1 Ambawang River. This study aims to delineate effective speed reading. The method used is descriptive quantitative form. The data collection technique using the technique of indirect communication. Data collection tool used is a test. Guided items to KEM sense, that is a mix between visual ability and the ability of cognition, then the KEM calculation examples for the above data can be determined KEM her. From the results of the arithmetic average read speed of 500 wpm data obtained; percentage of the results were obtained from the data content of reading comprehension 64%. The calculation of its KEM is 500 X 64% = 320 wpm. This latter figure (320 wpm) is an effective speed reading that already includes the measurement of two elements advocates reading activities, namely the ability of eye movements in viewing the symbols of the print and the ability to understand the content of reading. While the figure of 500 wpm it is the ability of the average read speed which does not yet include elements of the content of reading comprehension.Â Keyword: speed, effectively, readÂ